Dissecting the Vesicular Trafficking Function of IFT Subunits - Yang, Huihui; Huang, Kaiyao (Frontiers in Cell and Developmental Biology, 2020)
Intraflagellar transport (IFT) was initially identified as a transport machine with multiple protein subunits, and it is essential for the assembly, disassembly, and maintenance of cilium/flagellum, which serves as the nexus of extracellular-to-intracellular signal integration. To date, in addition to its well-established and indispensable roles in ciliated cells, most IFT subunits have presented more general functions of vesicular trafficking in the non-ciliated cells. Thus, this review aims to summarize the recent progress on the vesicular trafficking functions of the IFT subunits and to highlight the issues that may arise in future research.